Chemical ecology and bioactivity of triterpene glycosides from the sea cucumber Psolus patagonicus (Dendrochirotida: Psolidae) - Muniain, Claudia Cristina (2008)
Information on the chemical ecology and bioactivity of chemical compounds present in the sea cucumber Psolus patagonicus is provided through an interdisciplinary approach. The specimens studied were collected from two different and very distant sampling localities: Bridges Islands (Beagle Channel, Ushuaia, 54° 48′57″ S 66° 25′00″ W) at depths of 4 to 10 m by SCUBA diving, and from the scallop beds of Zigochlamys patagonica (39° 27′10″ S 55° 56′76″ W), at depths of 110 m and 115 m (43° 47′84″ S 59° 56′80″ W) by means of non-selective dredge in the South Atlantic Ocean.The secondary metabolites were isolated from complete adults by a combination of chromatographic methods and purified by high-performance liquid chromatography. They were characterized as triterpene glycosides through extensive spectroscopic analyses (nuclear magnetic resonance and fast atom bombardment mass spectroscopy) and chemical methods. A purified fraction containing Patagonicoside A as the main triterpene showed a high level of mortality against the brine shrimp Artemia salina and revealed different antifungal activity of Patagonicoside A and its desulphated glycoside (ds-Patagonicoside A) against the fungi Cladosporium fulvum, Fusarium oxysporum and Monilia sp., compared with a potent commercial antifungal product.